2003
DOI: 10.4049/jimmunol.170.5.2323
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Dendritic Cells in the Mouse Liver: Identification and Characterization of Four Distinct Populations

Abstract: Liver dendritic cells (DC) are believed to play important roles in liver immunity, autoimmunity, and in the regulation of hepatic allograft acceptance. However, limited information is available on the phenotypes and functions of DC in the liver. To address this issue, we isolated DC from murine liver using procedures that do not involve collagenase, and characterized the freshly isolated DC population that had not been subjected to in vitro expansion. Thence, based on the expression of CD4, B220, and CD11b, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
113
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(125 citation statements)
references
References 55 publications
8
113
1
3
Order By: Relevance
“…Upon activation with CpG oligonucleotides, liver DC produced massive amounts of IL-12, consistent with a previous report (10). Surprisingly, however, the levels were ϳ10 times higher than those of spleen DC, further supporting the dichotomy between their functions (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Upon activation with CpG oligonucleotides, liver DC produced massive amounts of IL-12, consistent with a previous report (10). Surprisingly, however, the levels were ϳ10 times higher than those of spleen DC, further supporting the dichotomy between their functions (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Our phenotypic data differ considerably from that of a recent report by Lian et al (10) who showed several subtypes of myeloid and pDC, but did not identify lymphoid DC displaying CD8␣ or DEC205. There are two differences between our methods that may in part explain the discrepant results.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…We also examined the level of plasmacytoid DCs in the IRF-4 Ϫ/Ϫ spleen. CD19 ϩ and NK1.1 ϩ cells were gated out to exclude B cells and natural killer (NK) cells, which are B220 ϩ and CD11c low , respectively (44). The proportion and the absolute number of CD11c int B220 ϩ plasmacytoid DCs in IRF-4 Ϫ/Ϫ spleen were not significantly different from those of the wild-type spleen (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Intrahepatic mononuclear cells were prepared according to previous publications with several modifications [18][19][20][21]. In brief, mice were killed by inhalation of carbon dioxide for an average of 5 min, following which, the abdomen was opened immediately, and the spleen was collected and put in ice-cold PBS.…”
Section: Isolation Of Intrahepatic Mononuclear Cellsmentioning
confidence: 99%